The Role of Sworn Brotherhoodship in Nomadic State Formation - Obrusánszky, Borbála (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2026)
In the social relations of ancient steppe horsemen, kinship bonds played a defining role. However, there was an ancient customary law that allowed non-kin tribal leaders to enter into strong and longterm agreements with each other, that way the foreign, non-kin contracting parties could also become adopted siblings. Unfortunately, the study of Eurasian blood oaths is currently not a priority within the research, and over the past nearly one and a half centuries, only some papers or analyses have been published on this topic. There is no comprehensive monograph on the subject, although references to sworn brotherhood and alliances sometimes appear in studies concerning the steppe tribes and alliances.